Self-initiated professional development (SI-PD) elements for Malaysian Vocational Colleges' TVET teachers using Fuzzy Delphi Method (FDM) - Abdul Rahman, Nur Leenna (Universiti Tun Hussein Onn Malaysia Publisher’s Office, 2022)
Self-Initiated Professional Development (SI-PD) has gained much attention lately due to increasing concern on the effectiveness of teachers’ professional development practice. It is also one of Ministry of Education (MOE) agenda in Malaysia Education Blueprint (MEB) 2013-2025 to transform Continuous Professional Development (CPD) by increasing Self-Initiated Professional Development (SI-PD) from 16 percent to 60 percent and reducing Ministry-led professional development by the year of 2025. Specifically, the aim of this study was to explore the elements required in Self-Initiated Professional Development (SI-PD) framework for TVET teachers in vocational colleges according to experts’ consensus. Fuzzy Delphi Method (FDM) was used as a tool in this study to explore the elements and data presented here were a part of a larger study which explored SI-PD among TVET teachers in Vocational Colleges. Nineteen experts were involved consisted of MOE officers, lecturers from universities and teacher training institutions who have at least five years of experience in teachers’ professional development and TVET. Based on the data analysis, the defuzzification values for all elements exceeded the minimum value 33.6 and therefore, the findings conclusively suggested that the experts have consensually agreed that there are ten elements required in Self-Initiated Professional Development (SI-PD). The ranking of the elements based on experts’ consensus was listed as follows, (1) Industrial attachment opportunity, (2) Attitude, (3) Understanding, (4) Collaborative environment, (5) School administrators’ role, (6) Strategy, (7) Readiness, (8) Autonomy, (9) Reward and (10) Professional development system. The findings were used to design Self-Initiated Professional Development (SI-PD) framework for TVET teachers in vocational colleges. This study also promotes the suitability of Fuzzy Delphi Method as a current research tool in the field of research on professional development. The proposed SI-PD elements can underpin TVET teachers’ professional learning and support the cultivation of Self-Directed Learning (SDL) which then enable changes in their teaching and learning practice to be more meaningful and effective.